2m+1=6m+2

Simple and best practice solution for 2m+1=6m+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+1=6m+2 equation:


Simplifying
2m + 1 = 6m + 2

Reorder the terms:
1 + 2m = 6m + 2

Reorder the terms:
1 + 2m = 2 + 6m

Solving
1 + 2m = 2 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
1 + 2m + -6m = 2 + 6m + -6m

Combine like terms: 2m + -6m = -4m
1 + -4m = 2 + 6m + -6m

Combine like terms: 6m + -6m = 0
1 + -4m = 2 + 0
1 + -4m = 2

Add '-1' to each side of the equation.
1 + -1 + -4m = 2 + -1

Combine like terms: 1 + -1 = 0
0 + -4m = 2 + -1
-4m = 2 + -1

Combine like terms: 2 + -1 = 1
-4m = 1

Divide each side by '-4'.
m = -0.25

Simplifying
m = -0.25

See similar equations:

| 8(31.25+-0.5)+4y=250 | | x^4+6x^2+2x=0 | | 21m+36=3m | | 14x-21=49 | | (1/6x-5)-(6/5-6x) | | 8(x-9)=12 | | -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x | | 193=-x+96 | | -9x-13=50 | | 60x-3x^/3x | | 7(2x+2)=-84 |

Equations solver categories